Internet addiction and network identity: features of development in student youth - Ol'ga Besschetnova; Elena Tsyglakova; Alexey Vikulov (Educação & Formação)
The purpose of the study is to detect the level of Internet addiction in student youth, identify the features of network identity formation, and substantiate the relationship between personality traits and addictive behavior. The paper reports on the results of an empirical study of pedagogical university students (n=248) utilizing a battery of diagnostic techniques and secondary analysis. The results show a moderate level of Internet addiction in most surveyed students and confirm its association with personality traits – extroversion/introversion, neuroticism and psychoticism, manipulative behavior, openness to experience, a situational attitude to norms and values to achieve one's goals, approval of one's actions by reference users of the social network, and the formation of one's image and Internet reputation. Among the causes of Internet addiction are the lack of time management, the uncontrollability of online staying; psychological dependence; the unwillingness to interrupt other activities and deliberate avoidance; and verbal aggression in case of inability to use online resources. Authors conclude that targeted secondary prevention programs, such as educational interventions and awareness activities, can effectively reduce Internet addiction and its associated risks among university students, as evidenced by improvements in network identity metrics and lower addiction levels during the control stage.